Pengurusan Program Pemulihan : Satu Analisis Berdasarkan Tahap Kesediaan untuk Berubah di Kalangan Penagih Dadah - Mohd. Rafidi, Jusoh (2004)
The purposes of this study were to determine the readiness for change amongst drug addicts whose undergone drug treatment and rehabilitation in one-stop center (pusat serenti), and their stages of change differences reflected to the treatment phases and addiction categories. The study applied the Transtheoretical of Change Model, which categorized the process of change in five stages, i.e Precontemplation, Contemplation, Preparation, Action, and Maintenance. To measure these stages, Stages of Change Scale adapted from URICA Scale was used. 120 inmates of Pusat Serenti Muar, Johor, were selected to participate in this study, which divided in four groups, by treatment phases and addiction categories, with 30 inmates of each group. The results indicated that the majority of the drug addicts whose undergone drug treatment and rehabilitation program were in Contemplation stage, followed by Action, Maintenance, Preparation, and Precontemplation. The results from the Independent Sample t-test indicated that there is a difference in stages of change amongst inmates in phase 1 and 4, but there is no differences in stages of change amongst inmates whose undergone treatment for the first time and relapse inmates.